The role of supervision of the head of room in the application of nursing care standards in inpatient Kendari City Hospital - Sauria, Niaty; Pritami, Rania Fatrizza; Kurniawan, Fajar; Rajab, Muhammad Al (Journal of Midwifery and Nursing, 2024)
This study aims to evaluate the relationship between the supervision of the head of the room and the implementation of nursing care standards in the Inpatient Room of Kendari City Hospital. With a sample of 53 respondents, the results showed a significant relationship between the supervision of the head of the room and the implementation of nursing care standards (?2 = 16,345, p = 0,000). Percentage analysis showed that the implementation of nursing care standards considered sufficient received a higher percentage (60.4%) compared to those considered less (11.3%). The implications of this study provide support for the role of room head supervision in improving the implementation of nursing care standards at Kendari City Hospital. Improvement recommendations include strengthening the supervision program, improving the implementation of nursing care standards, periodic monitoring and evaluation, improving communication, and involving nurses in decision making. These steps become an important foundation for improving the quality of nursing services, creating a work environment that supports the development and satisfaction of nurses in the hospital.